Household fish consumption in relation to fishing practices and fish production in flood plains of Bangladesh - Tsai, Chu Fa; Ali, Mohammad Youssuf; Ahsan, Kamrul; Alam, Sardar S (Indian Journal of Fisheries, 2011)
Situated in the Ganges River Delta, Bangladesh has one of the richest and largest flood-plainÂ· systems in the world (Rahman 1989). Its total areawas’eltimated to b.: 2 946 953 ha, occupying 72.81 % of the inland water area, and prooucfngltbout 50% of the total fish production of inland open water capture fisheries (Bangladesh Fisheries Resources Survey System 1988).